Regional Success After Brexit The Need for New Measures - de Ruyter, Alex (Emerald Publishing, 2019)
The Brexit vote has thrown up issues of the sharp regional disparities that divide the UK. The vote has been seen as a protest by those who felt left behind by globalization and hence a need for government policy to address regional disparities. As a result there has been a re-emergence of interest in an active industrial strategy. Using Scotland as a case study, this book argues that the contribution of regions outside the capital relative to London is under-reported. using the West Midlands as a second case study, the book posits that manufacturing is more important to the UK than financial services and that key to a successful strategy of economic re-balancing is a need to ensure adequate skills provision and essential infrastructure. The book will examine potential policy developments in the light of Brexit that would lead to economic re-balancing in the post-Brexit era.